Effect of Gamma-irradiation on Marigold (Tagetes erecta l.) Cut Flowers: Changes in Sensory and Physicochemical Properties and Lutein Content - Pal, Sayani; Bhattacharjee, Paramita (Journal of Postharvest Technology, 2016)
Marigold flowers packaged in low density polyethylene (LDPE) were  subjected to gamma irradiation in the dose range of 0.02-2.5 kGy and stored in  an environmental chamber (23±2°C, 80% R.H.) along with positive (non irradiated LDPE packaged flowers) and negative control (non-packaged, non irradiated flowers) sets for evaluation of their shelf-lives. Assays of sensory  and physicochemical parameters of senescence revealed that flowers irradiated  at 2.3 kGy had the highest shelf-life of 11 days, with a lead of 5 and 7 days  vis-à-vis positive and negative controls, respectively. This study established  for the first time the phenomenon of carotenogenesis (synthesis of ‘lutein’) in  both irradiated and non-irradiated marigold flowers, with highest production  and preservation of lutein in 2.3 kGy irradiated flowers. Thus gamma  irradiation can boost the export potential of this flower, both for its ornamental  and therapeutic value.
Keywords: Gamma-irradiation; Low density polyethylene Lutein; Marigold; Shelf-life